Rancang bangun mesin pengiris tempe otomatis - Hasan Hariri; Muhammad Al Fathar; Ivan Bachtiar (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2022)
Tempe slicer is one of the food industry machines that is still developing, however, in various parts of Indonesia the machine still uses the manual method for slicing tempe as its main raw material. With that, to maximize the production of tempe by developing an automatic tempe slicer to increase the capacity of the tempeh slices. The fabrication process of this machine includes planning, drawing design, frame assembly and others. The manufacture of this automatic tempe slicer goes through various stages such as: measuring, cutting, welding, painting, assembling and testing. The tempe slicer is designed using the main actuation, namely an electric motor and a knife to slice the tempe. This automatic tempe slicer is equipped with a blade driven by a shaft that generates power from an electric motor transmitted by the pulley and v-belt.